(untitled) (Development Service Industry Management, 2024)
Compared to off-line marketing, e-commerce occupies a much smaller market share, but it is developing dynamically every year. The main factors that stimulate the development of e-commerce may be the natural desire of mankind to use time more efficiently. It is important to note that the volume of transactions in the e-commerce segment varies significantly across industries. One of the main reasons for this is the level of development of e-commerce technologies, which can be divided into two areas: the level of convenience of product selection and the level of convenience of the purchase process. In order to increase the share of on-line sales, it is advisable to conduct a study of the use of digital marketing tools and formulate recommendations for their effective use. Increasing the company’s gross profit and reducing the cost of marketing activities is a systematic and important process. Due to the beginning of the development and implementation of Metaverse technologies, the marketing activities of enterprises require a reassessment of the strategic concept of development, taking into account the fundamental changes in the interfaces of interaction with users in VR (virtual reality) and changes in the level of detail of BI (business intelligence) tools. Given the dynamic development of the competitive environment and digital marketing technologies, it is necessary to develop effective models for the use of digital marketing tools. According to the growth forecast for e-commerce “E-commerce as a percentage of total retail sales worldwide from 2021 to 2027 [5], available on statista.com, the volume of e-commerce transactions as a percentage of total retail sales will increase from 20.1% in 2024 to 22.6% in 2027. According to the report “Google’s Advertising Revenue from 2001 to 2023” [5], the growth of Google’s revenue from advertising activities since 2019 has been 176.44%. Since 2019, Meta Platforms’ advertising revenue has increased by 189.43% [5]. As a result of the introduction of VR (Virtual Reality) technologies, the methods of advertising will be significantly changed, and it is now possible to start working with these technologies using Internet marketing tools: • use 3D product models on websites and mobile applications, optimizing the models (in terms of detail, perception, and work speed) and working to increase the conversion rate from page view to order; • use 3D models for advertising on the Google platform (currently, this technology is available only in the US for the categories of household goods and shoes). According to the Eurostat report “Internet purchases by individuals” [8] for 2023, it is possible to see that the level of retail on-line sales is declining from West to East. This circumstance indicates additional potential in the E-commerce sector for the EU and partner countries, which can be realized in the form of additional migration of sales from the off-line segment to the on-line one. The market volume in Ukraine in the E-commerce segment grew by 144.38% between 2017 and 2023, which indicates a shift in business focus from off-line to on-line sales. Based on the analysis, it is reasonable to state that for the active development of e-commerce in Ukraine, there will be a demand for the following specialists: project managers in the field of information technology, Internet marketers, UX/UI designers, Front End and Back End developers of websites and mobile applications. This will require the implementation of specialized educational programs, such as Internet Marketing, to train qualified staff in educational institutions to meet the market demand for specialists in this area. Based on the data of Baker Tilly Ukraine LLC [9] and the data of statista.com [5], the author analyzes the level of development/penetration of on-line sales in Ukraine and the United States, which allows us to conclude that there is a potential for additional growth of the share of on-line sales in Ukraine, taking into account the level of use of digital marketing tools. As a result of the research, advertising budgets were analyzed and an assessment of the dynamics of digital marketing tools development was formed. The level of migration of off-line sales to on-line is analyzed and a list of recommendations (hypotheses) for further development (increase) of the share of digital marketing in the relevant product categories is formed. A comparative analysis was done according to the level of sales with the help of digital marketing tools in Ukraine and the United States for the selected categories of goods.